Implementation of Gamification Strategies to Improve Autonomous Learning in Agroindustrial Engineering Students - Dávila Morán, Roberto Carlos (Journal of the University of Zulia, 2023)
The objective of the study was to evaluate the implementation of gamification strategies to improve autonomous learning in Agroindustrial Engineering students, at a public university in Lima-Peru. The materials and methods indicate that the study was basic, with a quantitative approach, non-experimental design and correlational scope. The population was 179 students of the eighth cycle of Agroindustrial Engineering. A probabilistic sampling was carried out, which yielded 104 students. To measure gamification strategies and their dimensions: dynamics, mechanics and components, a questionnaire with 21 items and five response alternatives was used. To measure autonomous learning and its dimensions: personal, institutional and didactic, a questionnaire with 20 items and five response options was used. The results of the descriptive analysis indicate that 49.0% and 50.0% of the students perceive a medium level in gamification strategies and autonomous learning, respectively. The findings of the inferential study reveal that gamification strategies are associated with the autonomous learning of Agroindustrial Engineering students, with p-value <0.005. Likewise, gamification strategies are associated with the personal, institutional and didactic dimensions of autonomous learning.